Implementing of Islamic Learning Integrated in Biology Education through Team Teaching Method to Enhance Students’ Understanding of Sex Education - Aldeva Ilhami; Nurhayati Zein; Suci habibah; Zulfahmi Zulfahmi; Niki Dian Permana; Dora Dayu Rahma Turista (Bioeducation Journal, 2021)
Sex education is needed due to increasing in teenager's sexually deviant behavior increase. The integration of Islamic values in biology learning is teachers' strategy to prevent free sex deviant behavior in the disrupssion digital era. The aim of this study was to determine the effect of the implementation of integrated Islamic biology learning with the team teaching method on students' understanding of sex education at SMA 12 Pekanbaru. The research design was a Quasi-experimental with one shot case study design. Population and sample are students at SMAN 12 Pekanbaru. Collection methods using tests and question-naires. The data analysis technique used is descriptive statistics. The results showed that the average level of understanding of students' sex education in the knowledge domain of students was 73% with a good category and an attitude domain of 79% with a good category. It can be concluded that the implementation of integrated Islamic biology learning with the team teaching method has a positive contribution to students' understanding of sex education. Biology and Islamic education teachers can collaborate in designing sex education learning as an effort to prevent adolescent sexual deviant behavior.